2007
DOI: 10.1097/coc.0b013e31804b40bb
|View full text |Cite
|
Sign up to set email alerts
|

Capecitabine Plus 3-Weekly Irinotecan (XELIRI Regimen) as First-Line Chemotherapy for Metastatic Colorectal Cancer

Abstract: XELIRI is an active first-line treatment of MCRC. Implementation of upfront dose reductions for both agents in patients with risk factors for toxicity appears to have produced a safer regimen compared with previous studies of XELIRI without such dose reductions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 39 publications
2
54
1
1
Order By: Relevance
“…Although a comparison of results from different phase II studies can be only speculative, the efficacy of our schedule is in line with that obtained by the other groups who have also published response data in phase II trials testing capecitabine -irinotecan combination regimens (Bajetta et al, 2004;Park et al, 2004;Borner et al, 2005;Cartwright et al, 2005;Kim et al, 2005;Rea et al, 2005;Patt et al, 2007;Choi et al, 2008) (Table 3). Indeed, our median TTP and OS are among the highest of those published to date with this combination.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Although a comparison of results from different phase II studies can be only speculative, the efficacy of our schedule is in line with that obtained by the other groups who have also published response data in phase II trials testing capecitabine -irinotecan combination regimens (Bajetta et al, 2004;Park et al, 2004;Borner et al, 2005;Cartwright et al, 2005;Kim et al, 2005;Rea et al, 2005;Patt et al, 2007;Choi et al, 2008) (Table 3). Indeed, our median TTP and OS are among the highest of those published to date with this combination.…”
Section: Discussionsupporting
confidence: 75%
“…In Table 3, which summarises the main grade 3 -4 toxicities per patient reported in previous phase II studies testing the combination of capecitabine and irinotecan, the improved tolerability of the 2-weekly regimen is notable: grade 3 -4 neutropenia and diarrhoea ranged between 5 -28 and 8 -34% in other phase II studies, respectively, compared with respective rates of 6 and 15% in this study. Unlike the current study, grade 3 -4 hand -foot syndrome was reported in most of those studies (Cartwright et al, 2005;Patt et al, 2007;Choi et al, 2008). Our regimen also appears to be associated with a lower rate of grade 3 -4 neutropenia (6 vs 24 -23%) and a similar rate of grade 3 -4 diarrhoea (15 vs 14 -11%) compared with FOLFIRI (Tournigand et al, 2004;Van Cutsem et al, 2007).…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…Following these reports, this combination therapy was recognized as the standard chemotherapy for colorectal cancer. Nonetheless, several studies have attempted to use oral fluoropyrimidine derivatives such as capecitabine and S-1, instead of 5-FU plus leucovorin, in combination with CPT-11 (11)(12)(13)(14). These studies have also shown favorable results in terms of their efficacy and safety.…”
Section: Introductionmentioning
confidence: 99%